Indoor air quality and ventilation - Clancy, Eoin (CIBSE knowledge series ;, 2011)
This guide presents an overview of indoor air quality (IAQ) in buildings, and outlines how IAQ impacts on occupants health and performance. Ideally the surrounding environment and facilities in a particular space should provide healthy conditions in terms of sufficient fresh air, low pollution concentrations, adequate lighting and heating, access to drinking water and catering areas, and satisfactory sanitary installations. Cooling and/or air conditioning may also be needed depending on climate conditions and internal heat gains. The building should also have security and fire/smoke protection systems to protect the occupants and the building fabric in the event of unwanted intrusion and the outbreak of a fire or other undesirable high risk event (e.g. flooding). --